THE EFFECT OF A FIRM’S CORPORATE SOCIAL RESPONSIBILITY (CSR) AND CORPORATE ENVIRONMENTAL RESPONSIBILITY (CER) ON FIRM PERFORMANCE ON THE CONSUMER STAPLES SECTOR - Eduard Ary Binsar Naibaho (Jurnal Penelitian Akuntansi (JPA), 2021)
A firm as an entity is one that exists within society, so it must have its responsibilities to uphold. Especially in recent times, people have become more critical of companies and how they behave, as well as the impacts they have on society and the environment around them. A firm’s corporate social responsibility (CSR) and corporate environmental responsibility (CER) are two factors that become heavily scrutinized due to this new development, as stakeholders become more sensitive to how a firm contributes back to society and how it takes care of the environment. If a firm is socially and environmentally responsible, it is arguable that it will receive more support and therefore perform better financially. Thus, this study is conducted to see if there is any tangible link between a firm’s financial performance and their CSR and CER disclosures. The main hypothesis is that both types of corporate responsibility have a positive effect on a firm’s financial performance. The sample size used includes 30 American firms listen in S&P500 within the customer staples sector, using data from the years 2016-2019 using the purposive sampling method. The data is analyzed using multiple regressions and the results show that while CSR has a clear positive correlation with a firm’s financial performance, CER has a more nuanced correlation, where it is generally positive unless the disclosure of irresponsibility is involved.